Respon Santri Al-Faqih II Terhadap Dakwah Gus Miftah di Tempat Hiburan Malam - Khatami, Mu'ayad; Aliyudin, Mukhlis; Abdul Ghani, Agi Muhammad (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The researcher has three objectives in this study: first, to find out the attention, understanding, and acceptance of Al-Faqih II students towards Gus Miftah's da'wah in nightclubs. The S-O-R (Stimulus-Organism-Response) theory is used in this study, with the application of theory: Stimulus, namely the way of preaching Gus Miftah in nightclubs, Organism, namely the students of Al-Faqih II Islamic Boarding School, and Response, namely the attitude of students towards the way of preaching Gus Miftah in places evening entertainment. The research method used is descriptive method, with this type of research using survey or field methods. The type of data in this study is quantitative. The results of the research on attention, understanding, and acceptance showed that Al-Faqih II students towards Gus Miftah's da'wah at nightclubs showed an average value (mean) of 4.03; 4.47; 4,28.